ANALISIS KESEHATAN BANK DENGAN METODE CAMEL (STUDI KASUS : PT. BANK TABUNGAN NEGARA, TBK PERIODE 2011-2015) - Ratna Kurnia Sari (Monex: Journal of Accounting Research, 2019)
Lately the term healthy or unhealthy bank is increasingly popular. Actual events, about banks such as mergers and liquidation are always linked to the health of the bank. Therefore, a bank certainly needs an analysis to know its condition after doing operational activities, especially in a certain period of time. The analysis is done here in the form of bank soundness rating. The health of a bank is a bank's ability to conduct normal banking operations and be able to full fill all its obligations well in ways in accordance with prevailing banking regulations. While the goal to be achieved in this study is to determine the financial performance of PT. Bank Tabungan Negara, Tbk reviewed based on bank health analysis using CAMEL method, 2011-2015 period. Data analysis method used here refers to comparative descriptive analysis, where the financial statements will be analysis in terms of capital, assets, management, earnings and liquidity in order to obtain comparison of results in each year, so it will appear the level of finance and performance of the bank. While the data source used in this study is secondary data in the form of documents of banking financial statements from 2011 to 2015 obtained from the website of PT. Bank Tabungan Negara, Tbk is www.btn.co.id. The results obtained are CAR, NPL, BOPO, NIM, ROA, ROE and LDR, PT. Bank Tabungan Negara, Tbk declared less healthy. This is due to a decrease in management terms. In addition, in terms of profitability (ROA and ROE) also occurred a decline that causes banks to establish reserve impairment losses due to increased ratio of non-performing loans or bad loans.